2006
DOI: 10.1152/ajpheart.00052.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac diastolic dysfunction in conscious dogs with heart failure induced by chronic coronary microembolization

Abstract: Left ventricular (LV) diastolic dysfunction is a fundamental impairment in congestive heart failure (CHF). This study examined LV diastolic function in the canine model of CHF induced by chronic coronary embolization (CCE). Dogs were implanted with coronary catheters (both left anterior descending and circumflex arteries) for CCE and instrumented for measurement of LV pressure and dimension. Heart failure was elicited by daily intracoronary injections of microspheres (1.2 million, 90- to 120-microm diameter) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The ratio of NF/left ventricle area (NF/LV) from all examined slices were calculated and averaged. Even slices (2,4,6,8,10) were used for light and transmission electron microscopic analysis.…”
Section: Evaluation the Areas Of No-flow Zonementioning
confidence: 99%
“…The ratio of NF/left ventricle area (NF/LV) from all examined slices were calculated and averaged. Even slices (2,4,6,8,10) were used for light and transmission electron microscopic analysis.…”
Section: Evaluation the Areas Of No-flow Zonementioning
confidence: 99%
“…Other investigators determined EDPVRs with EDV variation ranging from 25% to 50%. The numbers of cardiac cycles used were typically Ͻ10 in some studies (11,13,23,25). In the present study, the average EDV variation was 31 Ϯ 16% (relative to the maximum EDV) and the average diastatic volume variation was 40 Ϯ 21% (relative to the maximum diastatic volume).…”
Section: Determination Of the Edpvr And D-pvrmentioning
confidence: 48%
“…Kass et al previously demonstrated that increased coronary perfusion during IABP support improves tissue elasticity, a major determinant of diastolic dysfunction [18,19]. Similarly, Gill et al showed that the development of diastolic dysfunction was related to decreased coronary perfusion induced by recurrent coronary embolization [20]. Furthermore, metabolic disturbances and increased central blood volume both seem to be contributing factors for the development and continued prevalence of diastolic dysfunction [21].…”
Section: Discussionmentioning
confidence: 99%